EVALUATION OF ANTI-INFLAMMATORY AND ANTINOCICEPTIVE ACTIVITY OF TRIPHALA RECIPE - Sireeratawong, Seewaboon; Jaijoy, Kanjana; Soonthornchareonnon, Noppamas (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
The anti-inflammatory and antinociceptive activities of Triphala recipe were studied in animal models. Triphala recipe (4 mg/ear) significantly exhibited an inhibitory effect on the ear edema formation induced by ethyl phenylpropiolate-induced, but not on the arachidonic acid -induced ear edema in rats. Furthermore, Triphala recipe at the doses of 300, 600 and 1,200 mg/kg significantly reduced carrageenan-induced hind paw edema. Next, the anti-inflammatory action in chronic inflammation was measured using the cotton pellet-induced granuloma formation assay in rats. Triphala recipe (1,200 mg/kg) reduced neither transudative weight nor granuloma formation. It also did not affect on body weight gain and thymus weight indicating that Triphala recipe does not have a steroid-like effect. In antinociceptive study, Triphala recipe (300, 600, 1,200 mg/kg), elicited significant inhibitory effect on both phases, especially in late phase, of the formalin test in mice suggesting that the antinociceptive action of Triphala recipe may be via both peripheral and at least partly centrally acting.